THE DIALOGIC NATURE OF PERSONIFICATION IN THE POETICS OF WILLIAM BLAKE - Mirzayev, Jasur; Madalov, Navruz (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This research aims to find out whether the life of William Blake was reflected in his poems. The reason the author wants to analyze the poems and the biography of William Blake because the author found an interesting fact that Blake was said to be unschooled but he could make so many literary works.